2013
DOI: 10.1177/0093854813496999
|View full text |Cite
|
Sign up to set email alerts
|

The Validity and Reliability of the Violence Risk Scale–Youth Version in a Diverse Sample of Violent Young Offenders

Abstract: The Violence Risk Scale–Youth Version (VRS-YV; S. Wong, Lewis, Stockdale, & Gordon, 2004-2011) is a risk assessment and treatment planning tool for youths designed to assess violence risk, identify dynamic risk factors or treatment targets, and evaluate changes in risk from treatment or other change agents. We examined the psychometric properties of the VRS-YV on a diverse sample of 147 young offenders. The tool demonstrated high internal consistency (α = .90) and interrater reliability (intraclass correlation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 48 publications
(83 reference statements)
1
23
0
Order By: Relevance
“…Given that a poor family environment is a common risk factor for future violence and maladaptive behavior (Capaldi & Patterson, 1996;Farrington & Loeber, 2000;Loeber & Stouthamer-Loeber, 1986), its representation and subsequent convergence across both instruments is typical. Both instruments have previously demonstrated convergent validity with other dynamic specific violence risk inventories that largely comprise environmental and contextual items (Viljoen et al, 2012;Stockdale, Olver, & Wong, 2014). The SAVRY Historical domain additionally demonstrated a strong correlation with the YLS/CMI Education/Employment subscale, both of which comprise factors concerning school achievement.…”
Section: Discussionmentioning
confidence: 87%
“…Given that a poor family environment is a common risk factor for future violence and maladaptive behavior (Capaldi & Patterson, 1996;Farrington & Loeber, 2000;Loeber & Stouthamer-Loeber, 1986), its representation and subsequent convergence across both instruments is typical. Both instruments have previously demonstrated convergent validity with other dynamic specific violence risk inventories that largely comprise environmental and contextual items (Viljoen et al, 2012;Stockdale, Olver, & Wong, 2014). The SAVRY Historical domain additionally demonstrated a strong correlation with the YLS/CMI Education/Employment subscale, both of which comprise factors concerning school achievement.…”
Section: Discussionmentioning
confidence: 87%
“…Compared to the other meta-analyses on the YLS/CMI (Olver et al, 2009;Schwalbe, 2008), ten studies that were used in Olver et al (2009) were included in these meta-analyses (Gossner & Wormith, 2007;Marczyk, 2002;McKinnon 2004;Morton, 2003;2008;Rowe, 2002;Schmidt, Hoge, & Gomes, 2005;Stockdale, 2008;van de Ven, 2004;Viljoen et al;2008). Three studies that were used in the study completed by Schwalbe (2008) met all of the criteria for inclusion, and were therefore included in this study (Flores, 2004;Rowe, 2002;Schmidt, Hoge, & Gomes, 2005).…”
Section: Methods For Locating Studiesmentioning
confidence: 99%
“…A correct prediction would be that someone who is low risk does not reoffend, and an incorrect prediction is that someone who is low risk does reoffend. Several studies have found that there is no significant difference with how well the instrument predicts recidivism for girls and for boys (Barnes, 2013;Campbell et al, 2014;Flores, 2013;Gossner, 2003;Jung & Rawana, 1999;Schmidt, Hodge, Gomes, 2005;Stockdale, 2008;). …”
Section: Yls/cmi -Previous Findingsmentioning
confidence: 99%
See 1 more Smart Citation
“…As such, change scores may not predict long-term offending that spans over an 8-year follow-up period. Similarly, a dissertation on the Violence Risk Scale: Youth Version (VRS:YV; Lewis, Wong, & Gordon, 2004) did not find significant associations between change scores and reoffending in a subsample of 22 youth (Stockdale, 2008).…”
Section: Dynamic Change Hypothesis: Changes In Risk Will Predict Reofmentioning
confidence: 99%